In vivo Illustration of Altered Dopaminergic and GABAergic Systems in Early Parkinson's Disease - Takashima, Hirotsugu; Terada, Tatsuhiro; Bunai, Tomoyasu; Matsudaira, Takashi; Obi, Tomokazu; Ouchi, Yasuomi (Frontiers in Neurology, 2022)
Background: Changes in γ-aminobutyric acid (GABA) function are noted in patients with Parkinson’s disease (PD) who have some nonmotor impairments. However, dopamine-related GABA function and GABA-related cognitive changes are still unclear. Methods: Thirteen drug-naive early-stage PD patients underwent a series of PET scans with [11C]flumazenil(FMZ) and [11C]CFT. The [11C]FMZ binding potential (BPND) derived from a Logan plot analysis was compared between PD patients and age-matched controls. The [11C]CFT radioactivity relative to the cerebellar counterpart was estimated as a semiquantitative value [11C]CFT SUVR. Correlations between [11C]FMZ BPND and [11C]CFT SUVR in the same region of interest were also examined. Results: In patients in the PD group, [11C]CFT SUVR was significantly lower in the putamen. The levels of [11C]FMZ BPND in the cerebral cortex (frontal lobe dominancy) and the affected-side putamen were also reduced. In addition, [11C]CFT SUVR was negatively correlated with the [11C]FMZ BPND level in the affected-side putamen. In patients in the PD group, the total frontal assessment battery (FAB) score was positively correlated with the [11C]FMZ BPND in the frontal region. Conclusion: GABAergic dysfunction coexists with dopaminergic loss not only in the putamen but also over the extrastriatal region in patients with early PD and is related to frontal dysfunction. The negative correlation of [11C]CFT SUVR with [11C]FMZ BPND in the affected putamen suggests that a greater dopaminergic demise would decelerate GABA release (or an increase in tracer binding), resulting in persistent failure of the GABAergic system in PD patients.